An institutional analysis of Sibalom Natural Park-Protected Area Management Board on community-based ecotourism in Sibalom, Antique - Atienza, Perlyn F.; Pingoy, Whelannie Y. (Miagao, Iloilo University of the Philippines in the Visayas, 2007)
This is an exploratory and evaluative study aimed to conduct an institutional analysis of the Protected Area management Board (PAMB) specifically, in the management of Sibalom Natural Park (SNP) in Sibalom, Antique. Seventeen (17) representatives from the three (3) member-institutions of PAMB and two 92) People's Organizations (POs) were chosen through purposive interview as respondents. Focused group discussion (FGD) and key informant interview (KII) were utilized to gather necessary data. KII used structured interview. secondary data from the different member-institutions of PAMB were also sources of essential information needed in the study. The performance of PAMB in managing the SNP was analyzed based on the four components of management. These four components were delegations of functions, utilization of financial resources., conflict management, and leadership and mandates. It was found out that the SNP-PAMB members' responsibilities were not clearly defined and there was no strict delianeation of each of the member-institutions' roles and functions. Since, the organization does not have enough funds to sustain its existing projects and to initiate new ones, projects and activities were financed through the individual efforts of the mmembers. Though there is lack of coordination among mmembers, they do not consider it as conflict. Factors such as unstable financial status, limited activities, lack of clear institutional structure hinder the implementation of the existing mandates for the operations of PAMB.
Research Project (Undergraduate, Bachelor of Arts in Community Development) -- Miagao, iloilo : University of the Philippines Visayas, March 2007.
Keywords: Natural Park -- Sibalom, Antique; Community-Based Ecotourism -- Sibalom, Antique; Sibalom Natural Park-Protected Area Management Board